Natural Genetic Diversity in Tomato Flavor Genes - Pereira, Lara; Sapkota, Manoj; Alonge, Michael; Zheng, Yi; Zhang, Youjun; Razifard, Hamid; Taitano, Nathan K.; Schatz, Michael C.; Fernie, Alisdair R.; Wang, Ying; Fei, Zhangjun; Caicedo, Ana L.; et al. (Frontiers in Plant Science, 2021)
Fruit flavor is defined as the perception of the food by the olfactory and gustatory systems, and and is one of the main determinants of fruit quality. Tomato flavor is largely determined by the balance of sugars, acids and volatile compounds. Several genes controlling the levels of these metabolites in tomato fruit have been cloned, including LIN5, ALMT9, AAT1, CXE1 and LoxC. The aim of this study was to identify any association of these genes with trait variation and to describe the genetic diversity at these loci in the red-fruited tomato clade comprised of the wild ancestor Solanum pimpinellifolium, the semi-domesticated species Solanum lycopersicum cerasiforme and early domesticated Solanum lycopersicum lycopersicum. High genetic diversity was observed at these five loci, including novel haplotypes that could be incorporated into breeding programs to improve fruit quality of modern tomatoes. Using newly available high-quality genome assemblies, we assayed each gene for potential functional causative polymorphisms and resolved a duplication at the LoxC locus found in several wild and semi-domesticated accessions which caused lower accumulation of lipid derived volatiles. In addition, we explored gene expression of the five genes in nine phylogenetically diverse tomato accessions. In general, the expression patterns of these genes increased during fruit ripening but diverged between accessions without clear relationship between expression and metabolite levels.